PROSES PEMBUATAN LENGIS TANDUSAN DI DESA DAWAN KLOD, KABUPATEN KLUNGKUNG DALAM FOTOGRAFI STORY - Ida Ayu Eka Shanti; Amoga Lelo Octaviano; I Made Bayu Pramana (Lp2mpp Isi Denpasar - Ps. Fotografi, 2021)
Lengis Tandusan is coconut oil that is traditionally processed and has a distinctive aroma, since the COVID-19 pandemic the production and distribution of lengis Tandusan has been slow. However, this home-based business is still running, it can even continue to grow so as to provide creative ideas by visualizing the Process of Making Lengis Tandusan in Dawan Klod Village, Klungkung Regency in Story Photography and aiming to develop creativity and apply photography techniques in the creation of works. The creation of this photographic work began with collecting data through scientific books, journals and news. The creation process carried out direct observations in the field, conducted interviews on the manufacture of barren lengis in order to obtain complete data and took photos. From the results of the photo shoot, it is continued with the process of selecting the best photos, followed by the editing and printing process and the final stage, namely the exhibition. The result of the creation of the process of making barren lengis in the arrangement of 15 photographic works with the title A Coconut Picker, Coconut Middleman, Separating Coconut Shells, Peeling Coconuts, Grated Coconut Flesh, Grated Coconut Flesh, Coconut Squeezing, Woman Taking Saang, Nandusin, Stirring Coconut Milk, Filtering Klengis, Final Process, Lengis Tandusan, Mepes Klengis and Saur. The techniques used in the creation of this work include frog eye view, eye level, bird eye view, high angle, framing and lighting utilizing natural light from sunlight and artificial light from external flash as fill in light or additional light in the process of shooting the work. photography. Keywords: Lengis Tandusan, Dawan Klod Village, Klungkung, Traditional, Story Photography